ASM652: Business process / Faculty of Business Management - UiTM, Faculty of Business Management (2022)
This course focuses on concepts and methodology for business process redesign (BPR). Emphasis is placed on business process redesign principles, transformation principles, and continuous process improvement principles. Apart from BPR, students are also exposed to process improvement approach.